Some Legal Controversies Regarding Party-affiliated Endowments and Their Participation in Business Activities: The Case of EFFORT and TIRET Endowments - Messelu, Mamenie; Markides, Professor Costas (Bahir Dar University Journal of Law, 2023)
Social service needs in no way can be fulfilled by the government alone. That is why governments are giving due consideration for Civil Society Organizations (hereinafter CSOs) and incorporating them in their legal frameworks. Charitable endowment is among the different classifications of CSOs, which play a significant role in every walk of life as they fill the gaps that the government fails or is unable to discharge its responsibility in various dimensions including human rights protection and socioeconomic development. In Ethiopia, party affiliated endowments such as Endowment Fund for the Rehabilitation of Tigray (EFFORT), Amhara National Regional State Rehabilitation and Development Fund (TIRET), Endowment Foundation for the Development of Oromia (TUMSA), and Endowment Fund for the Development of Southern Nation Nationalities and Peoples (WENDO) are established by Tigray Peoples Liberation Front (TPLF), Amhara National Democratic Movement (ANDM), Oromia Peoples Democratic Organization (OPDO), and Southern Nation Nationalities and Peoples Democratic Movement (SEPDM) respectively, on the assumption that the wider public of each regional state community is the beneficiary of these endowments. This article examined the legality of formation, registration, and operation of these endowments and their participation in business by using EFFORT and TIRET endowments as a case study. The article upholds doctrinal legal research which is based on the identification, synthesis and analysis of the law defining endowment and their participation in business. The finding shows that there is defective formation of EFFORT and TIRET endowments, and also that their involvement in business activities is contrary to the provisions of the laws regarding commerce, tax, competition, and CSOs.